2022
DOI: 10.7759/cureus.28923
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging: Evolution, Significance, and Deficit

Abstract: Bioimaging is a digital technology-based medical advancement which is still relatively new. It has to do with real-time visualization of biological processes. This innovative imaging technology combines anatomical structure with functional data such as electric and magnetic fields, motion which is mechanical, and metabolism to provide information on anatomical structure. It's a non-invasive procedure that gives you a bird's-eye view of the human body, with more depth and detail as you go. As a result, bioimagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Conventional techniques such as X-ray computed tomography (CT) are widely employed in the medical field, but they face limitations in rapidly providing detailed images of microstructures. [210] Numerous NPs have been explored for anticancer bioimaging due to their small size, which grants them strong permeability and retention -a phenomenon that allows NPs to accumulate in tumorigenic areas. [211] Various carbon nano allotropes similar in size and shape to CDs have been investigated for this purpose.…”
Section: Cds In Bioimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional techniques such as X-ray computed tomography (CT) are widely employed in the medical field, but they face limitations in rapidly providing detailed images of microstructures. [210] Numerous NPs have been explored for anticancer bioimaging due to their small size, which grants them strong permeability and retention -a phenomenon that allows NPs to accumulate in tumorigenic areas. [211] Various carbon nano allotropes similar in size and shape to CDs have been investigated for this purpose.…”
Section: Cds In Bioimagingmentioning
confidence: 99%
“…Depending on the target and techniques utilized, bioimaging can be categorized into molecular, biomedical, drug delivery, and computational bioimaging. Conventional techniques such as X‐ray computed tomography (CT) are widely employed in the medical field, but they face limitations in rapidly providing detailed images of microstructures [210] …”
Section: Cds – Bioimagingmentioning
confidence: 99%
“…On this basis, Jain and research team [ 88 ] reported combining MOFs with various QD types can produce a hybrid with superior qualities compared to the separate components, exhibit stability including their excellent proportion of signal-to-noise, excellent sensitivity, profound penetration, and lack of tissue self-fluorescence interference and be employed for bioimaging and drug administration. Adding more, due to their functionalization, compositions, customized structure, and porosity, MOF-based nanocomposites have gained widespread recognition in positron emission tomography (PET), optical imaging (OI), computed tomography (CT), and magnetic resonance imaging (MRI) for intracellular imaging [ 153 ]. Magnetic resonance imaging (MRI) …”
Section: Mofs Applications In the Biomedical Fieldmentioning
confidence: 99%
“…Bioimaging has emerged as an increasingly crucial technique for disease diagnostics and management, owing to its non-invasiveness, near real-time feedback, high accuracy, and reliability 1 , 2 . Optical imaging, which provides high-resolution images without the need for radioactive contrast agents, has been further strengthened by advancements in nanotechnology 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%